Analysis of Business Strategy Plan on MCU at Sartika Asih Bandung - Purwadi Purwadi; Ratih Tresnati; Albert Hendarta (Enrichment : Journal of Management, 2022)
Not optimal facilities, services, minimal customer visits and market share opportunities that have not been maximized from the Unit MCU are the problems behind this research. The purpose of this study is to describe the current condition of the MCU Unit and to describe the analysis of the business strategy plan for the development of the Unit MCU based on SWOT, BMC and BSC. The type of research used is descriptive qualitative. The research method used is Case Study. The object of research is Sartika Asih Hospital, Bandung. Data collection techniques using interviews, observation and documentation. The data analysis technique is Content Analysis & Context Analysis and validated through the technique and time triangulation method. The results showed that the Business Strategy Plan for the unit MCU includes strategic plans and business plans, based on SWOT analysis, BMC, BSC and a combination of BMC and BSC. Sartika Asih Hospital Bandung has sufficient strength to take advantage of existing opportunities. The strategy in managing the Unit MCU must be managed by identifying existing threats and weaknesses and overcoming them with the strengths and opportunities they have. Aspects of the business plan which includes corporate, capacity, marketing, personnel and financial aspects must be able to be a way to achieve the goal of becoming a Unit MCU Professional, Accurate, Fast and Affordable.